2020
DOI: 10.3390/polym12081820
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-Surface Modification of Nanoparticles for Developing Highly-Crosslinked Polymer Nanocomposites

Abstract: Surface modification of nanoparticles with functional molecules has become a routine method to compensate for diffusion-controlled crosslinking of thermoset polymer composites at late stages of crosslinking, while bulk modification has not carefully been discussed. In this work, a highly-crosslinked model polymer nanocomposite based on epoxy and surface-bulk functionalized magnetic nanoparticles (MNPs) was developed. MNPs were synthesized electrochemically, and then polyethylene glycol (PEG) surface-functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Table 1 suggests that increasing β from 5 to 15 °C min −1 increased both T P and Δ H , as expected from previous investigations [ 48 ]. The presence of Mica and Mica-IM in the epoxy nanocomposites causes a reduction in the T onset , which is a signature of the facilitation of the cure, except for the first rate of heating, 5 °C min −1 .…”
Section: Resultssupporting
confidence: 87%
“…Table 1 suggests that increasing β from 5 to 15 °C min −1 increased both T P and Δ H , as expected from previous investigations [ 48 ]. The presence of Mica and Mica-IM in the epoxy nanocomposites causes a reduction in the T onset , which is a signature of the facilitation of the cure, except for the first rate of heating, 5 °C min −1 .…”
Section: Resultssupporting
confidence: 87%
“…It is observed that the major decomposition reaction of PU occurs above 300 • C, which is attributed to degradation of soft segments. The minor weight loss in the range of 150 to 250 • C suggests degradation of hard segments and evaporation of volatile compounds [42][43][44][45]. Addition of nano-clay stabilized thermal decomposition of the matrix and the TGA curves of nanocomposites were very much similar to the one for pure PU.…”
Section: Resultsmentioning
confidence: 82%
“…For CDs, the broad bands between 3500 and 3000 cm −1 correspond to the stretching vibrations of O-H and N-H, respectively, 15 which can be utilized as connection points for PEG. Besides, C-H stretching vibrations at 2926 and 2876 cm −1 , CH 2 vibrations at 1465 and 1399 cm −1 , 16 C=O/C=C bonds at 1660 cm −1 , and C-N bonds at 1560 cm −117 could be observed in the FITR spectrum of the CDs (red line in Figure 1E). After connection with PEG, the FTIR spectrum of PEG-CDs (black line in Figure 1E) shows significant changes.…”
Section: Resultsmentioning
confidence: 91%